Erratum: International changes in COVID-19 clinical trajectories across 315 hospitals and 6 countries: Retrospective cohort study (Journal of Medical Internet Research (2021) 23:10 (e31400) DOI: 10.2196/31400) - Weber, Griffin M.; Zhang, Harrison G.; L'Yi, Sehi; Clara-Lea, Bonzel; Hong, Chuan; Avillach, Paul; Gutiérrez-Sacristán, Alba; Palmer, Nathan P.; Li Min Tan, Amelia; Wang, Xuan; Yuan, William; Gehlenborg, Nils; et al. (JMIR Publications, 2021)
In “International Changes in COVID-19 Clinical Trajectories Across 315 Hospitals and 6 Countries: Retrospective Cohort Study” (J Med Internet Res 2021 Oct 11;23(10):e31400), two errors were noted. In the originally published paper, equal contribution of the last three authors was not noted. This has been corrected to add a note of equal contribution to the last three authors, as well as to add a statement to the Authors' Contributions section denoting the nature of equal contributions. In the originally published paper, an equal contribution footnote was applied to authors Griffin M Weber, Harrison G Zhang, and Sehi L'Yi. In the corrected paper, the equal contribution footnote has been applied to authors Griffin M Weber, Harrison G Zhang, Sehi L'Yi, Tianxi Cai, Andrew M South, and Gabriel A Brat. The Authors’ Contribution section has been updated to include the following statement: These authors contributed equally: GMW, HGZ, SL. These authors jointly supervised the work: TC, AMS, GAB. The correction will appear in the online version of the paper on the JMIR Publications website on November 30, 2021, together with the publication of this correction notice.